On the use and misuse of climate change projections in international development. (14th March 2019) - Nissan, Hannah; Goddard, Lisa; de Perez, Erin Coughlan; Furlow, John; Baethgen, Walter; Thomson, Madeleine C.; Mason, Simon J.
Abstract : Climate resilience is increasingly prioritized by international development agencies and national governments. However, current approaches to informing communities of future climate risk are problematic. The predominant focus on end‐of‐century projections neglects more pressing development concerns, which relate to the management of shorter‐term risks and climate variability, and constitutes a substantial opportunity cost for the limited financial and human resources available to tackle development challenges. When a long‐term view genuinely is relevant to decision‐making, much of the information available is not fit for purpose. Climate model projections are able to capture many aspects of the climate system and so can be relied upon to guide mitigation plans and broad adaptation strategies, but the use of these models to guide local, practical adaptation actions is unwarranted. Climate models are unable to represent future conditions at the degree of spatial, temporal, and probabilistic precision with which projections are often provided, which gives a false impression of confidence to users of climate change information. In this article, we outline these issues, review their history, and provide a set of practical steps for both the development and climate scientist communities to consider. Solutions to mobilize the best available science include a focus on decision‐relevant timescales, an increased role for model evaluation and expert judgment and the integration of climate variability into climate change services. This article is categorized under: Climate and Development > Knowledge and Action in Development Abstract : Approximate time horizons of decision‐making in the agricultural sector, shown using a rough logarithmic scale. Very few decisions in agriculture have a time horizon longer than about 30 years.